Phytochemical composition of ipomoea batatas and moringa oleifera leaves and crackers from underutilised flour - Owusu, Deborah (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the Degree of Master of Science,